Gain-of-function Naᵥ1.8 mutations in painful neuropathy - Faber, Catharina G; Lauria, Giuseppe; Merkies, Ingemar S. J; Cheng, Xiaoyang; Han, Chongyang; Ahn, Hye-Sook; Persson, Anna-Karin; Hoeijmakers, Janneke G. J; Gerrits, Monique M; Pierro, Tiziana; Lombardi, Raffaella; Kapetis, Dimos; et al. (Proceedings of the National Academy of Sciences - PNAS, 2012)
Painful peripheral neuropathy often occurs without apparent underlying cause. Gain-of-function variants of sodium channel Na ᵥ1.7 have recently been found in ∼30% of cases of idiopathic painful small-fiber neuropathy. Here, we describe mutations in Na ᵥ1.8, another sodium channel that is specifically expressed in dorsal root ganglion (DRG) neurons and peripheral nerve axons, in patients with painful neuropathy. Seven Na ᵥ1.8 mutations were identified in 9 subjects within a series of 104 patients with painful predominantly small-fiber neuropathy. Three mutations met criteria for potential pathogenicity based on predictive algorithms and were assessed by voltage and current clamp. Functional profiling showed that two of these three Na ᵥ1.8 mutations enhance the channel’s response to depolarization and produce hyperexcitability in DRG neurons. These observations suggest that mutations of Na ᵥ1.8 contribute to painful peripheral neuropathy.